The Effectiveness of Edible Coating Aloe Vera (Aloe vera chinensis L.) in Inhibiting Enzymatic Browning on Sliced Apples - Risky mawardi; Nanik Suhartatik; Merkuria Karyantina (JITIPARI, 2023)
Apple is a fruit that turn brown quickly after being cut. One method to maintain the quality of apples cut is coating the fresh-cut apples with an edible coating. Ediblei coatingi is a thini ilayer that can bei eaten and can keep the iquality ofi the icoated material. Thei study aimed toi determinei the effectiveness of edible coating aloe vera (Aloe vera chinensis L.) in inhibit enzymatic browning reaction. The designii wasi usiing icompletely irandomized idesign. The first factor was the citrus species (Citrus aurantifolia, Citrus hystrix DC, Citrus amblycarpa) iand the secondi factori was thei istorage itime (0, 3, 6 day). Edible coating applied to fresh-cut apples and tested for moisture content, total dissolved solids, weight loss, color, overall appearance, vitamin C and total plate count. Thei resultsi ishowed that aloe vera edible coating with citrus extract was not effective in inhibiting the enzymatic reaction of sliced apples. The type of citrus and storage time was affect the effectiveness of aloe vera edible coating. Citrus amblycarpa extract has a lower water content reduction effect with a water content of 54.51% on the 6th day of storage time and has an effect on the total plate count, that Citrus amblycarpa extract has decreased total plate count in day 6th. Citrus aurantifolia extract gives the effect of maintaining brightness compared to other types of citrus, with a brightness value of 58,290 on the 6th day. The type of citrus has no effect on weight loss, total dissolved solids, overall appearance. The length of storage has an effect on the effectiveness of aloe vera edible coating, the longer it is stored, the apples cut will decrease in quality.